Hair cortisol levels in women with medically unexplained symptoms. (February 2022) - Fischer, Susanne; Skoluda, Nadine; Ali, Nida; Nater, Urs M.; Mewes, Ricarda
Abstract: Stress has been demonstrated to be involved in the development of medically unexplained symptoms. A key underlying mechanism could be lower levels of cortisol, which can contribute to symptoms such as fatigue or pain. However, the literature is highly equivocal, which may be due to methodological limitations inherent in short-term cortisol assessment. The aim of this case-control study was to investigate, for the first time, whether individuals with different forms of medically unexplained symptoms show altered hair cortisol concentrations, a long-term marker of hypothalamic-pituitary-adrenal functioning. Two groups of women with medically unexplained symptoms were recruited. The first had a functional somatic syndrome, characterised by specific medically unexplained symptoms (i.e., chronic fatigue syndrome, fibromyalgia, or irritable bowel syndrome, n = 33). The second had somatic symptom disorder, characterised by excessive thoughts, feelings, and behaviours devoted to various medically unexplained symptoms (n = 23). These groups were contrasted with healthy controls (n = 30), and women with depression (n = 27). Cortisol representing the previous three months was extracted from hair. Chronic stress and childhood trauma were assessed (retrospectively). Women with somatic symptom disorder had lower hair cortisol than healthy controls and women with functional somatic syndromes. No differences in hair cortisol were found between healthy controls, functional somatic syndromes, and depression. Neither childhood trauma nor chronic stress was correlated with hair cortisol. Provided that our findings are replicated, they may suggest that hypocortisolism is found in a specific subgroup of individuals with medically unexplained symptoms, and potentially in those characterised by excessive thoughts, feelings, and behaviours about symptoms.